2014
DOI: 10.1093/protein/gzu015
|View full text |Cite
|
Sign up to set email alerts
|

Autolytic degradation of ocriplasmin: a complex mechanism unraveled by mutational analysis

Abstract: Ocriplasmin, a truncated form of plasmin, is commercialized in the USA and in Europe under the trade name Jetrea(®), and indicated for the treatment of symptomatic vitreomacular adhesion and vitreomacular traction including when associated with macular hole ≤400 µm, respectively. We have shown in a previous study that ocriplasmin undergoes autolytic degradation when injected in eye vitreous, which leads to its rapid inactivation. In order to investigate this process further, we have introduced in ocriplasmin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The autolytic and mixed variants also exhibited reduced K cat and V max values. This results were in agreement with Noppen et al [17]. Also, reduced K cat and V max values was observed in variant with A59T mutation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The autolytic and mixed variants also exhibited reduced K cat and V max values. This results were in agreement with Noppen et al [17]. Also, reduced K cat and V max values was observed in variant with A59T mutation.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies revealed that initial cleavage occurs at position 156-157 because it is faster and after this cleavage, sensitivity of the other two sites to autolytic cleavage greatly enhances [27]. Cleavage at 156-157 site was caused inactivation, and mutant with cleavage at 177-178 site was detected in wild-types [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vigilant monitoring and pars plana vitrectomy constitute standard procedures for managing symptomatic vitreomacular adhesion [ 1 , 3 ]. Given the risk of damage to the retina caused by the surgery [ 7 ], proteolytic enzymes such as plasmin have been examined for the enzymatic release of retinal traction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%